Poverty Alleviation Through the Refinement of Zakat Policy Recommendation, Aceh Case - Habibul Abrar; Chairul Iqbal Aziz (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Around 3 billion people are living in poverty and around 35 % of them are from Muslim World. Aceh with its 5.3 million citizens, 98% of which are Muslims, is a great could be a great case study. Aceh is the poorest province in Sumatra Island and fourth poorest nationwide. The Gini coefficient is increasing. There is a method of poverty alleviation and inequality eradication is Islam, it is called Zakat. Zakat is basically a wealth distribution system that has worked in many countries. Aceh implements the system as well. However, there are some improvements necessary for the system to work better. Zakat money is susceptible to politicization of governors. There is a big possibility of zakat money overlapping with other government programs. The implementation of zakat money tends to be not very efficient. There is also a problem of inequality of opportunity to be a receiver of zakat money. This paper intends to give recommendation for the improvements. Most of the improvements are reflected from how Malaysia implement their zakat system. A business advertising method is also used as an inspiration for the recommendations.